Pelvic fixation for neuromuscular scoliosis deformity correction - Dayer, Romain (Current Science Inc., 2012)
Pelvic fixation is most frequently indicated in the pediatric population for the treatment of neuromuscular scoliosis with significant pelvic obliquity. Neuromuscular scoliosis surgery is associated with a high risk of complications, and this is further increased by extension of fusion to the sacrum. Numerous techniques have been described for pelvic fixation associated with a long spine fusion each with its own set of specific benefits and risks. This article reviews the contemporary surgical techniques of pelvic fixation used to extend a spine fusion to the sacrum and pelvis focusing on the management of neuromuscular scoliosis, including their biomechanical rationale, results, and complications.